INDONESIA'S COMMITMENT TO THE UNITED NATIONS PEACEKEEPING OPERATIONS IN CONSTRUCTIVIST PERSPECTIVE: CASE STUDY OF ROADMAP VISION 4,000 PEACEKEEPERS 2015-2019 POLICY - Murwanto, Ilham Pradana; Rosyidin, Mohamad; Susiatiningsih, Rr. Hermini; Paramasatya, Satwika (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
Roadmap Vision 4,000 Peacekeepers 2015-2019 is Indonesia's foreign policy in the era of President Joko Widodo's administration related to Indonesia's participation in the UN PKO (United Nations Peacekeeping Operations). This policy is aimed at placing 4,000 active Garuda Contingent troops at the end of 2019. Roadmap Vision 4,000 Peacekeepers contains a strategic reference for the Indonesian government from 2015 to 2019 to reach the target of 4,000 troops. This study focuses on analyzing this policy using constructivist perspective with the concept of role identity, to explain why Indonesia behaves in that perspective. The purpose of this study is to enrich the perspective of Indonesia's foreign policy related to participation in UN PKO, especially in the era of the President Joko Widodo using the non-material aspects of constructivist. This study uses a research methodology in the form of literature studies and interviews with related practitioners, while data analysis used is congruent methods to match the theories used with case studies. This study was done to see how the identity of Indonesia's role as a peacemaker state was realized through the Roadmap Vision 4,000 Peacekeepers. The results of this study prove that the role of Indonesian peacemaker will always reflect that role in every era of government because it has become a constitutional mandate in the 1945 State Constitution